A new Telipogon from Mexico close to Telipogon standleyi (Orchidaceae: Oncidiinae) - Bogarín, Diego (2013)
A new Telipogon from Mexico, previously confused with T. standleyi from Costa Rica, is described and illustrated. Telipogon amoanus is recognized by the pink-purplish flowers, the obliquely ovate, subfalcate sepals, the elliptic, entire petals, the triangular sagittate lip, densely pilose column with short basal hairs, and the pollinarium with the stipe obtrullate. Telipogon standleyi is illustrated based on Costa Rican material to facilitate species comparison. Additional comments on both species are provided.